Cover Feature: Light‐Activated Rhenium Complexes with Dual Mode of Action against Bacteria (Chem. Eur. J. 13/2020). Issue 13 (30th January 2020) - Frei, Angelo; Amado, Maite; Cooper, Matthew A.; Blaskovich, Mark A. T.
Abstract : The synthesis and characterization of a blue‐light‐activated rhenium tricarbonyl complex with antibacterial activity against methicillin resistant S. aureus and colistin resistant E. coli are described. Distinct activity profiles are observed in the presence and absence of light. Cellular uptake experiments in different E. coli mutants and synergy experiments with other antibiotics point to two distinct modes of action. More information can be found in the Full Paper by A. Frei, M. A. T. Blaskovich, et al. on page 2852 .